Optimalisasi Pengelolaan Sampah Laut Desa Adat Kedonganan Melalui Solusi Pengelolaan Sampah Menjadi Lampu Hias - Ni Kadek Cahyani; Luh Putu Mahyuni (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Kedonganan Village is a village with a fairly adequate level of infrastructure development. The people of Kedonganan Village are very dependent on tourism activities. In early 2021 the village experienced bad weather conditions. Heavy rainfall that lasted for several days resulted in an increase in the amount of sea water, which in turn caused an increase in the amount of waste shipped to the Kedonganan coast. This community service activity aims to provide shipping waste management solutions with creative ideas. The series of activities begins with observation of the area then a discussion process with relevant stakeholders. Followed by efforts to identify the characteristics and types of waste, checking the volume of waste generated within a certain period of time, then managing wood waste into economic value-added products in the form of decorative lighting furniture products. This service activity succeeded in creating a positive impact in an effort to provide a solution for managing this shipment of waste into creative decorative lighting products with economic value. This activity is expected to trigger other creative ideas from other villagers.